The Hierarchy of Intellect in Islamic Philosophy as a Framework for Critique of the Epistemological Limits of Artificial General Intelligence - Sedef Karakaş; Nihan Durmaz; Melis Yeşilçayır (Yayasan Albahriah Jamiah Indonesia, 2026)
The development of Artificial General Intelligence (AGI) has given rise to claims of cross-domain cognitive abilities that are equal to human rationality. However, these claims are still dominated by the computational paradigm, which reduces intelligence to symbolic processing and algorithmic optimization, thereby leaving an epistemological gap regarding the ontological status of knowledge and reflective consciousness that has not been widely studied from an Islamic philosophical perspective. This study specifically aims to reconstruct the hierarchy of intellect in Islamic philosophy as a critical conceptual model to test the epistemological limits of AGI and formulate a typology of ontological differences between the actualization of human intellect and computational architecture. The method used is a literature study with a philosophical-analytical approach through a systematic selection of classical and contemporary texts, a conceptual analysis of the categories of potential, actual, and acquired intellect, and an ontological comparison based on an analytical framework that assesses the dimensions of representation, consciousness, and transformation of the subject. The results show that the hierarchy of intellect is a multilevel process of actualization from potential to actuality through existential intensification, namely the improvement in the quality of the knowing subject’s existence, characterized by the integration of cognition, self-reflection, and meaning-making. Within this framework, knowledge is understood as the ontological transformation of the subject, not simply the accumulation of representations. In contrast, AGI operates at the representational-instrumental level through symbol manipulation, statistical learning, and probabilistic calculations that generate correlations and predictions without involving reflective awareness or changes in the subject’s ontological status. This finding confirms the structural and principal epistemological limits of AGI.